Design of fleet inventory application system Perum DAMRI - Mohamad Hasanudin; Ito Riris Immasari; Akmal Budi Yulianto (Yayasan Bina Internusa Mabarindo, 2022)
Assets are the most important resource for individuals or an organization that owns them, because assets are equipment that supports the activities of an organization. Over time the assets in the company will experience many changes (accretions and reductions) that apply very quickly and that also happens to Perum Damri. To support operational activities, Perum Damri still uses a semi-computerized system that uses Microsoft Excel in asset management and inventory of existing fleets. It is less efficient in terms of time, power as well as cost. The development of technology, can be used to overcome some of the obstacles faced today such as by creating a system that helps in asset management, fleet inventory to prevent damage, loss or